The Role of IL-37 in allergic Rhinitis, Asthma and Urticaria Diseases in Samples of Iraqi patients - Kadhem, Ashwaq A. (Iraqi Journal of Science, 2024)
Interleukin 37 (IL37) is an anti-inflammatory cytokine, secreted by monocytes, macrophages, and epithelial cells, which suppress the immune system through binding to one of the receptors and co-receptors of the IL-1R family. Different allergic disease phenotypes may be related to different biomarkers, and many mechanisms involve in the pathogenesis of allergic inflammations, so it is wealthy to study different cytokines to understand their effect on allergic diseases. Blood specimens were obtained from patients attending the Allergic Specialized Center/Baghdad-Resafa 74 patients with allergic diseases (rhinitis patients 24, asthma patients 26, urticaria patients 24 (37 men and 37 women) and 14 healthy control subjects (7 men and 7 women). Total and differential counts of WBC were determined, and total immunoglobulin E (IgE), and IL-37 concentration in serum were measured by the enzyme-linked immunosorbent assay ELISA. IL-37 levels were decreased in all types of patients whether in male or female in comparison with the control group with significant differences (p<0.05), that’s may due to the inactive signaling of IL-37 which leads to inflammatory diseases, through Th2 activation and secrete allergic pro-inflammatory cytokines that contribute to exacerbation pathogenesis of allergic diseases.